The Current Role of Arthroscopy in Traumatic Wrist Injuries: An Expert Survey - d'Ailly, Philip N.; Mulders, Marjolein A.M.; Coert, J. Henk; Schep, Niels W.L.; Members of IWAS (Journal of Wrist Surgery, 2022)
Background Wrist arthroscopy has become increasingly popular for diagnosing and treating traumatic wrist injuries. How wrist arthroscopy has influenced the daily practice of wrist surgeons remains unclear. The objective of this study was to evaluate the role of wrist arthroscopy for the diagnosis and treatment of traumatic wrist injuries among members of the International Wrist Arthroscopy Society (IWAS).Methods An online survey was conducted among IWAS members between August and November 2021 with questions regarding the diagnostic and therapeutic importance of wrist arthroscopy. Questions focused on traumatic injuries of the triangular fibrocartilage complex (TFCC) and scapholunate ligament (SLL). Multiple-choice questions were presented in the form of a Likert scale. The primary outcome was respondent agreement, defined as 80% answering similarly.Results The survey was completed by 211 respondents (39% response rate). The majority (81%) were certified or fellowship-trained wrist surgeons. Most respondents (74%) had performed over 100 wrist arthroscopies. Agreement was reached on 4 of the 22 questions. It was agreed that the outcomes of wrist arthroscopy strongly depend on surgeons' experience, that there is sufficient evidence for the diagnostic purposes of wrist arthroscopy, and that wrist arthroscopy is better than magnetic resonance imaging (MRI) for diagnosing TFCC and SLL injuries. No agreement was reached on the preferred treatment of any type of TFCC or SLL injury.Conclusion There is agreement that wrist arthroscopy is superior to MRI for diagnosing traumatic TFCC and SLL injuries, yet experts remain divided on the optimal management. Guidelines need to be developed for the standardization of indications and procedures.Level of Evidence This is a Level III study.
Keywords: wrist arthroscopy; survey; IWAS; ligaments; traumatic wrist injuries; TFCC; scapholunate